Comparison between SIRS and qSOFA Score for Predicting Mortality and Length of Stay Sepsis Patients in ICU of Dr Moewardi Hospital Surakarta - Tameru, Rahma Pramatama; Supraptomo, Rth; Setijanto, Eko (Smart Medical Journal, 2022)
Introduction: Sepsis is still one of the causes of morbidity and mortality in patients who are hospitalized. Early recognition and therapy is needed to prevent deterioration of the disease and predict outcomes. The Third International Consensus Definitions for Sepsis and Septic Shock in 2016 issued the latest definition for sepsis and recommended qSOFA score to replace the previous assessment system, SIRS criteria. This study was conducted with the aim of knowing the accuracy of the SIRS criteria, the accuracy of the qSOFA score, and the comparison between the two for predicting the mortality rate and length of stay of sepsis patients at the ICU of Dr Moewardi Hospital SurakartaMethods: This research was an observational analytic study with cross sectional approach, conducted in Dr Moewardi Hospital on September-November 2018. The samples were 106 sepsis patients. The data were collected by reading the medical record of sepsis patients who were hospitalized in ICU during of period July 2017 until June 2018 and analyzed statistically by and ROC curve analysis, chi square analysis test, and zero-truncated regression poisson testResult: qSOFA Score Pre-ICU (Sens 67.9%, Spe 50%, p=0.120, OR=2.111), qSOFA Score ICU (Sens 63.1%, Spe 77.3%, p=0.001, OR=5.813), SIRS Criteria Pre-ICU (Sens 88.1%, Spe 18.2%, p=0.439, OR=1.644), and SIRS Criteria ICU (Sens 84.5%, Spe 40.9%, p=0.009, OR=3.781). AuROC in predict mortality for qSOFA Pre-ICU, SIRS Pre-ICU, qSOFA ICU, and SIRS ICU were 0.625, 0.503, 0.754, and 0.644 consecutively. AuROC in predict length of stay in ICU > 3 days for qSOFA Pre-ICU, SIRS Pre-ICU, qSOFA ICU, and SIRS ICU were 0.580, 0.566, 0.681 and 0.639 consecutively. Conclusion: The qSOFA score has poor sensitivity and moderate specificity, while the SIRS criteria has high sensitivity but low specificity. But, qSOFA is superior to SIRS for predicting mortality and length of stay in ICU > 3 days. Keyword : Sepsis, ICU, SIRS, qSOFA,mortality